2017
DOI: 10.3390/su9081338
|View full text |Cite
|
Sign up to set email alerts
|

Association between Three-Dimensional Built Environment and Urban Air Temperature: Seasonal and Temporal Differences

Abstract: Climate change and the urban heat island phenomenon are increasingly important issues in urban thermal environments. However, there is a lack of research on the relationship between three-dimensional built environments and air temperature. Therefore, the purpose of this study is to provide policy suggestions that could be used to improve urban thermal environments by analyzing the effect of the three-dimensional built environment of an urban space on the urban air temperature according to changes in time (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Second, selecting a time period for each season is also challenging. For example, Park et al [13] designated spring, summer, fall, and winter as April, August, October, and January, respectively. Notably, a few studies have divided the season based on climate conditions or by examining whether the average temperature is higher or lower than a certain degree [18,56].…”
Section: Literature Review: Effect Of Urban Factors On Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Second, selecting a time period for each season is also challenging. For example, Park et al [13] designated spring, summer, fall, and winter as April, August, October, and January, respectively. Notably, a few studies have divided the season based on climate conditions or by examining whether the average temperature is higher or lower than a certain degree [18,56].…”
Section: Literature Review: Effect Of Urban Factors On Temperaturementioning
confidence: 99%
“…The fundamental theories regarding the influence of building geometry on UHI were developed earlier by Nunez and Oke [9] and Oke [10], which has led to several empirical studies in recent years [9,10]. These studies focused on morphological indicators such as the sky view factor (SVF), urban porosity, and surface roughness [11][12][13]. Moreover, they suggested that the geometric configuration of buildings can affect the urban temperature both directly and indirectly by influencing other factors such as solar radiation and ventilation performances [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Average sky view factors (viewshed analysis; ArcGIS v10.5; e.g. Park et al 2017) for SRG and DRG indicate slightly more topographic shading and consequently a slightly lower share of clear sky visibility in the more elongated valley / cirque of DRG compared to the wider SRG cirque. For SRG an average sky view factor of 0.64 and for DRG of 0.61 is computed (with a standard deviation of 0.03 for both).…”
Section: Study Areamentioning
confidence: 99%
“…Simulation‐based methods have been developed to estimate the SVF on a large scale based on the digital surface model (DSM) and 3D building models (Chen et al., 2012). However, the simulation‐based method relies heavily on the high quality of DSM or 3D building models, which leads to the problem of affordability (Lindberg & Grimmond, 2010; Park, Ha, & Lee, 2017).…”
Section: Introductionmentioning
confidence: 99%